Death of the Author: A Study to Explore the Author’s Perspective and Position in Bapsi Sidhwa’s The Crow Eaters - Pervaiz, Kawish (Journal of Research in Humanities, 2023)
The focal point of this research paper is to put emphasis on the role and dynamics of an author in the creation of a literary piece of work and study the various aspects of being an author by analyzing Bapsi Sidhwa’s The Crow Eaters. This research explores the positioning of Parsi community by a Parsi writer while also focusing upon the author’s imaginative and realistic strands involved in the portrayal of a particular community. While highlighting the role of an author, this research particularly sheds light upon the narratology of Bapsi Sidhwa and how it moves from specific to the universal by giving a voice to the margins. There are numerous researches exploring the role of the author, while this research examines and questions the distant and detached position of an author which creates a relationship of perception between the narrative and the reader. Roland Barthes’ “What is an Author” is used as a theoretical background for this research paper. This approach assists in comprehending the various stages and dynamics of a narrative. Future Researchers can probe literary theory and how an author and a narrative is analyzed from more than one perspective by literary critics.